Determining Motivation Factors Among Special Education Teachers In Teaching Students With Special Needs - Rodzi, Faidz Ikhwan; Mukhlis, Nur Hidayah; Mahrif, Nursuria (School of Social Sciences, USM, 2017)
The training of Special education teachers have been given attention by the Ministry of Education, Malaysia. According to Sufean (2004), since 1996 special education was given the same priority as other areas in the development of education in Malaysia. In order to implement effective teaching and learning in special education program as well as to motivate them in teaching special need students, teachers should be prepared and understand about the program itself. Therefore, this study is aimed to investigate factors that contribute to the motivation among special education teachers in teaching students with special needs. This study aims to investigate contributing factors of motivation levels among special education teachers toward the special needs children. Maslow Theory of Needs comprises of five (5) main predictors to determine the level of motivation among special education teachers which are physiological, safety, love and belongingness, esteem, self-actualization is applied as the instrument in this study. Since this is a concept paper, the result used is from 31 teacher respondents of Integrated Learning Disability of Special Education Program at Sekolah Kebangsaan Laksamana, Kuching.